Characterization of a Type VI Secretion System vgrG2 Gene in the Pathogenicity of Burkholderia thailandensis BPM - Li, Jin; Hu, Wei-wei; Qu, Guo-xin; Li, Xiao-rong; Xiang, Yi; Jiang, Peng; Luo, Jiang-qiao; He, Wen-huan; Jin, Yu-jia; Shi, Qiong (Frontiers in Microbiology, 2022)
Burkholderia thailandensis is a clinically underestimated conditional pathogen in the genus Burkholderia, the pathogenicity of the infection caused by B. thailandensis remains poorly understood. According to previous studies, Type-VI secretion system (T6SS) is a protein secreting device widely existing in Gram-negative bacilli. Valine-glycine repeat protein G (VgrG) is not only an important component of T6SS, but also a virulence factor of many Gram-negative bacilli. In one of our previous studies, a unique T6SS vgrG gene (vgrG2 gene) was present in a virulent B. thailandensis strain BPM (BPM), but not in the relatively avirulent B. thailandensis strain E264 (E264). Meanwhile, transcriptome analysis of BPM and E264 showed that the vgrG2 gene was strongly expressed in BPM, but not in E264. Therefore, we identified the function of the vgrG2 gene by constructing the mutant and complemented strains in this study. In vitro, the vgrG2 gene was observed to be involved in the interactions with host cells. The animal model experiment showed that the deletion of vgrG2 gene significantly led to the decrease in the lethality of BPM and impaired its ability to trigger host immune response. In conclusion, our study provides a new perspective for studying the pathogenicity of B. thailandensis and lays the foundation for discovering the potential T6SS effectors.